2013
DOI: 10.1002/elps.201200342
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid‐dependent protection against alkali‐burned human corneal cells

Abstract: Hyaluronic acid (HA) is a high‐molecular‐weight glycosaminoglycan and extracellular matrix component that promotes cell proliferation. This study aimed to evaluate the effects of HA on alkali‐injured human corneal epithelial cells in vitro, and to elucidate the mechanisms by which HA mediates corneal cell protection. A human corneal epithelial cell line (HCE‐2) was treated with sodium hydroxide before incubation with low‐molecular‐weight HA (LMW‐HA, 127 kDa) or high‐molecular‐weight HA (HMW‐HA, 1525 kDa). A gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
17
0
2
Order By: Relevance
“…We believe this to be the result of an inability of this highly viscous gel to penetrate into the cells (2). In a separate study, Wu et al (5) show that high molecular weight (HMW)-HA (1525 kDa) has superior cytoprotective effects compared to low molecular weight (LMW)-HA (127 kDa). HMW-HA 0.3% facilitates cell migration and wound healing (5).…”
Section: Tissue Regenerationmentioning
confidence: 98%
See 2 more Smart Citations
“…We believe this to be the result of an inability of this highly viscous gel to penetrate into the cells (2). In a separate study, Wu et al (5) show that high molecular weight (HMW)-HA (1525 kDa) has superior cytoprotective effects compared to low molecular weight (LMW)-HA (127 kDa). HMW-HA 0.3% facilitates cell migration and wound healing (5).…”
Section: Tissue Regenerationmentioning
confidence: 98%
“…HA has recently been used in several in vitro studies (2)(3)(4)(5). Our group has used HA jellies at concentrations of 2%, 4% and 8% that were formulated at the Placentary Histotherapy Center in Cuba from residual umbilical cords of human placentas obtained according to the National Recollection Program.…”
Section: Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wodewotzky et al 29 showed that HA can improve cell viability and increases cell proliferation in bone marrow-derived canine mesenchymal stem cells in vitro. Wu et al 49 showed that these beneficial effects Competing interests: none declared. Conflict of interests: none declared.…”
Section: What Is the Lubricin?mentioning
confidence: 99%
“…Hyaluronic acid serves other important biologic roles, including the ability to promote wound healing. Numerous studies have demonstrated that hyaluronic acid accelerates corneal wound healing both in vitro and in vivo . Consequently, topical hyaluronic acid is commonly included in the treatment regimen for superficial corneal ulcerations in canine patients.…”
Section: Introductionmentioning
confidence: 99%